Respuesta :

Answer:

Simplifying

9x + -2 + -13x + 16 = 0

Reorder the terms:

-2 + 16 + 9x + -13x = 0

Combine like terms: -2 + 16 = 14

14 + 9x + -13x = 0

Combine like terms: 9x + -13x = -4x

14 + -4x = 0

Solving

14 + -4x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-14' to each side of the equation.

14 + -14 + -4x = 0 + -14

Combine like terms: 14 + -14 = 0

0 + -4x = 0 + -14

-4x = 0 + -14

Combine like terms: 0 + -14 = -14

-4x = -14

Divide each side by '-4'.

x = 3.5

Simplifying

x = 3.5

Step-by-step explanation:

Answer:

-4x+14

Step-by-step explanation:

Collect "Like Terms" (9x and -13) = -4x

-4x - 2 + 16= -4x + 14